Delivery and Inventory for Industrial Support Company Using Web-based Application - Yuki Estrada; Tony Wibowo (ConCEPt - Conference on Community Engagement Project, 2024)
With the growing economic industry, companies are striving to be able to attain their client's trust with their services. By improving their system and operational activities, this may be able to decide and lead a company's future success. PT XYZ is a gas company that lacks an integrated and efficient system for their delivery operations. This problem resulted in data inconsistencies and time-consuming checking on their admins. Making an integrated information system is one of the methods to assist in solving this problem. Hence, a website for inventory and delivery was developed for PT XYZ aiming to be more efficient and facilitate organized documentation. The website was uploaded to hosting and its access was given out to PT XYZ.